Peat-derived hard carbon electrodes with superior capacity for sodium-ion batteries. Issue 34 (27th May 2020) - Adamson, Anu; Väli, Ronald; Paalo, Maarja; Aruväli, Jaan; Koppel, Miriam; Palm, Rasmus; Härk, Eneli; Nerut, Jaak; Romann, Tavo; Lust, Enn; Jänes, Alar
Abstract : A synthesis method has been developed to turn peat, cheap biomass into hard carbons that demonstrate high capacity and excellent sodium storage capability as anode material in sodium-ion batteries. Abstract : Herein we demonstrate how peat, abundant and cheap biomass, can be successfully used as a precursor to synthesize peat-derived hard carbons (PDCs), applicable as electrode materials for sodium-ion batteries (SIB). The PDCs were obtained by pre-pyrolysing peat at 300–800 °C, removing impurities with base–acid solution treatment and thereafter post-pyrolysing the materials at temperatures ( T ) from 1000 to 1500 °C. By modification of pre- and post-pyrolysis temperatures we obtained hard carbons with low surface areas, optimal carbonization degree and high electrochemical Na + storage capacity in SIB half-cells. The best results were obtained when pre-pyrolysing peat at 450 °C, washing out the impurities with KOH and HCl solutions and then post-pyrolysing the obtained carbon-rich material at 1400 °C. All hard carbons were electrochemically characterized in half-cells ( vs. Na/Na + ) and capacities as high as 350 mA h g −1 at 1.5 V and 250 mA h g −1 in the plateau region ( E < 0.2 V) were achieved at charging current density of 25 mA g −1 with an initial coulombic efficiency of 80%.